Pengaruh Live Streaming dan Metode Pembayaran Cash On Delivery Terhadap Keputusan Pembelian Pada Tiktok Shop di Indonesia - Ria Nofita Praptiwi; Indra Hastuti; Taufiq Nur Muftiyanto (Journal of Management and Social Sciences, 2024)
The rapid development of digital technology, especially the internet, has driven the emergence of a new marketing strategy known as digital marketing. One example of digital marketing in Indonesia is TikTok Shop, which offers attractive features such as live streaming, discounts, and cash on delivery payments. The objective of this research is to determine the influence of live streaming, and cash on delivery payment methods, both simultaneously and partially, on purchasing decisions on TikTok Shop in Indonesia. The research methodology employed is quantitative. Purposive sampling was used as the sampling technique. Data was collected using questionnaires and analyzed using IBM SPSS Statistics 25, with multiple linear regression analysis. The results showed that live streaming, cash on delivery payment methods have a significant simultaneous influence on purchasing decisions. Partially, live streaming and cash on delivery payment methods have a positive influence on purchasing decisions. The coefficient of determination (R²) is 89.6%, indicating that live streaming, cash on delivery payment methods, have an influence on purchasing decisions, while the remaining 10.4% is influenced by other variables.